Strong Far-Field Vertical Excitation and Building Damage: A Systematic Review and Future Avenues - Dipendra Gautam; Rewati Baruwal (Advances in Civil Engineering)
Strong vertical excitation may lead to detrimental consequences on structures and infrastructures. To date, the impacts of strong vertical shaking on structures and infrastructures are considered for near-field regions only. However, anomalies in terms of recorded evidence and damage occurrence in the central Himalayan earthquakes dragged the attention of the researchers to explore the possibility of strong vertical shaking in far-field regions as well. Systematic review approach is used to sum up the findings from scholastic works reported to date and juxtaposed the findings with the evidence from central Himalayan earthquakes. It is concluded that the strong vertical shaking in the far-field is undeniable, at least in the central Himalayas; thus, incorporation of strong far-field vertical shaking in structural analysis and design is required. This paper reports the evidence reported in the literature for strong vertical shaking and adds evidence from Nepal focusing on strong far-field vertical excitation.